A systematic review and meta-analysis of neuromuscular electrical stimulation post-botulinum toxin injection in children with cerebral palsy - Fu-An Yang; Jie-Ren Mi Le; Chia-Hsiang Lu; Chao-Chun Huang; Hung-Chou Chen (Scientific Reports)
Abstract The aim of our study is to investigate whether adjunct neuromuscular electrical stimulation (NMES) therapy improves functional performance outcomes in children with cerebral palsy (CP) who have received botulinum toxin (BTX) injections. We searched the PubMed, Cochrane Library, CINAHL, EMBASE, and Scopus databases for randomized controlled trials studying the effects of NMES after BTX injection in children with CP from database inception to July 3, 2024. Two independent reviewers extracted data, and risks of bias were assessed using the PEDro scale for randomized controlled trials. We included 5 randomized controlled trials in this meta-analysis. NMES treatment following BTX injection resulted in greater functional performance outcomes compared with BTX injections alone (standardized mean difference = 0.57; 95% CI = 0.22 to 0.92). However, NMES following BTX injections did not significantly improve spasticity outcomes (standardized mean difference = 0.28; 95% CI = − 0.21 to 0.76). Despite including only a small number of trials, the present analysis demonstrated that NMES is an effective adjunct to BTX injections for managing CP in children. Further research must be conducted to refine these therapies, ensure better outcomes, and alleviate the burdens faced by individuals with CP.